Market Power of the German Beer Industry on Export Markets - An Empirical Study - - Thomas Glauben; Jens-Peter Loy (Kiel University, Department of Food Economics and Consumption Studies, 1999)
In this paper the existence and magnitude of market power for the German beer exporters is tested. Two theoretical approaches to model incomplete competition on international markets are employed, the "pricing to market" (PTM) model the "residual demand elasticity" (RDE) approach. Estimations for both models over the period from 1991 to 1998 reveal incompatible results regarding the underlying theoretical models and with respect to the approach that is used. While significant market power is indicated in the PTM model, the RDE approach signalizes perfect competition. This leads to the conclusion that the underlying theoretical models have to be extended to consistently match the observed market solutions in this case.
Keywords: 330; Brauerei; Export; Marktmacht; Außenhandelspreis; Betriebliche Preispolitik; Schätzung; Theorie; Deutschland; Welt